2019
DOI: 10.1177/0741932519849660
|View full text |Cite
|
Sign up to set email alerts
|

Reading Interventions for Students With or At Risk of Attention-Deficit/Hyperactivity Disorder: A Systematic Review

Abstract: Empirical evidence suggests inattention and attention-deficit/hyperactivity disorder (ADHD) are related to reading fluency, reading comprehension, and academic failure. Students with ADHD are served in both general and special education settings, but limited research explores effective reading interventions for this population. The purpose of this synthesis is to investigate reading studies for participants identified with or at risk of ADHD. We address the following research question: What are the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
(129 reference statements)
1
25
0
Order By: Relevance
“…Findings from the present review and systematic review identified in the most recent search by Stewart and Austin (2020) are complementary. The present review offers a summary of reading comprehension abilities in ADHD, highlighting where these individuals tend to struggle most, while the systematic review by Stewart and Austin (2020) offers evidence for strategies that are most effective in improving reading outcomes in this population.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Findings from the present review and systematic review identified in the most recent search by Stewart and Austin (2020) are complementary. The present review offers a summary of reading comprehension abilities in ADHD, highlighting where these individuals tend to struggle most, while the systematic review by Stewart and Austin (2020) offers evidence for strategies that are most effective in improving reading outcomes in this population.…”
Section: Discussionmentioning
confidence: 86%
“…Findings from the present review and systematic review identified in the most recent search by Stewart and Austin (2020) are complementary. The present review offers a summary of reading comprehension abilities in ADHD, highlighting where these individuals tend to struggle most, while the systematic review by Stewart and Austin (2020) offers evidence for strategies that are most effective in improving reading outcomes in this population. Importantly, the present review found that individuals with ADHD demonstrated reduced performance on all tasks that required them to summarize or identify main story ideas and these skills were the focus of many reading interventions identified in the recent systematic review.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The visual analysis provided an evaluation of level, trend, and stability ( Lane and Gast, 2014 ) whereas a non-parametric approach for analyzing single-case data, Tau-U ( Parker et al, 2011 ) was calculated for the dependent variable to determine the effect of the intervention. Several studies showed that the interpretation of the Tau-U is ranged as follows: weak (0.20 or less), moderate (0.21–0.59), and strong or large (0.60 or greater) ( Parker et al, 2011 ; Vannest and Ninci, 2015 ; Harrison et al, 2019 ; Stewart and Austin, 2020 ). The analysis of Tau-U scores suggests that the MLT and GoTalk NOW app were strong and largely effective in developing requests, and the weighted average of Tau-U was 0.63.…”
Section: Resultsmentioning
confidence: 99%
“…In the particular case of school failure, systematic reviews have been carried out to address research questions that allow us to understand the possible causes of this phenomenon. Over the last year, we have seen systematic review studies that focus on such topics as the role of classmates in the development of social anxiety in adolescents [5]; populations of students with attention deficit hyperactivity disorder [6]; the relationship between academic achievement and school discipline [7]; as well as academic programs and interventions to increase the interest and participation of children and youth with disabilities in education or STEM careers [8].…”
Section: Introductionmentioning
confidence: 99%